(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an in-depth exploration of the classification of English consonants, focusing on their articulation and acoustic properties. It categorizes consonants by place of articulation (e.g., bilabial, alveolar), manner of articulation (e.g., plosives, fricatives), and voicing (voiced or voiceless sounds). Practical applications of this classification are highlighted in areas such as language teaching, speech therapy, and linguistic research. The article also addresses common challenges in consonant production for non-native speakers and contextualizes English consonants within the broader spectrum of global phonetic systems. This comprehensive overview emphasizes the importance of understanding consonant systems in language learning and scientific inquiry, offering insights into the mechanics of speech and the universal principles of phonetics. It concludes by underscoring the role of consonant classification in fostering effective communication, bridging linguistic diversity, and advancing language-related studies.